Corticotomy-Assisted Orthodontic Treatment: A Literature Review - Athanasia Patatou; Niovi Iacovou; Paraskevi Zaxaria; Michail Vasoglou; Georgios Vasoglou (Oral, 2023)
The increased number of adults seeking orthodontic treatment has led to the need for faster results as social limitations arise with the use of fixed or even removable appliances. Corticotomy-assisted orthodontic treatment (CAOT) has been proposed as a technique that accelerates tooth movement and leads to a substantial reduction in treatment time. This review was conducted by searching four databases for original articles about CAOT, review articles and articles about alternative techniques and periodontal effects up to 31 December 2022. The aim of the review was to present the historical and biological background of CAOT, the description of the technique and some alternative and less invasive techniques that have been proposed. Indications, contraindications and periodontal side effects are also discussed.